STRATEGI PERCEPATAN PENGEMBANGAN PLTS ATAP DI INDONESIA - I Ketut Wiriana (LPSDI Bina Patria, 2025)
Rooftop Solar Power Plants (PLTS Atap) are a strategic solution in supporting the clean energy transition and achieving the renewable energy mix target in Indonesia. With abundant solar energy potential, the development of rooftop solar systems is crucial to strengthening national energy resilience. However, the actual installed capacity of rooftop solar remains far below the national target, necessitating a comprehensive acceleration strategy. This study aims to analyze policies, quota systems, technical approaches, and cross-sector collaboration as key factors in accelerating rooftop solar deployment in Indonesia. The analysis shows that progressive policies, such as the Minister of Energy and Mineral Resources Regulation No. 2 of 2024—which eliminates capacity and export-import restrictions while offering economic incentives—provide a strong motivation for consumers. Moreover, the implementation of a managed quota system, targeted to reach 1.5 GW by 2028, ensures the stability of the national electricity grid. Technical approaches, including public education and installer training, are also essential to successful implementation. Collaboration among government, industry, and civil society plays a central role in expanding rooftop solar adoption. With an integrated strategy and consistent policy support, rooftop solar is expected to become a key pillar in driving Indonesia’s transition to a low-carbon energy future.